Synthesis and anti-bacterial activity of a library of 1, 2-benzisothiazol-3(2H)-one (BIT) derivatives amenable of crosslinking to polysaccharides. Issue 13 (30th March 2017) - Viani, Fiorenza; Rossi, Bianca; Panzeri, Walter; Merlini, Luca; Martorana, Alessandra M.; Polissi, Alessandra; Galante, Yves M.
Abstract: 1, 2-Benzisothiazol-3(2H)-one (BIT) is one of the most common chemical biocides in industrial products, with a heterocyclic structure and a wide range of antimicrobial activity. A library of BIT derivatives was synthesized and characterized, from which 18 compounds were selected, tested for anti-bacterial activity relative to the parent molecule and amenable of coupling to plant polysaccharides in general and to galactomannans (GM) in particular, widely used as rheology modifiers, but with limited "biostability". Four sites on the BIT core were targeted: the nitrogen and the oxygen atoms on the heterocyclic ring, the C5 and the C6 positions on the aromatic ring, where functional groups were introduced. The ultimate aim of this work is to establish whether by covalently linking a biocide to GM polymers, their "biostability" can be improved. Graphical abstract: Highlights: A library of 1, 2-benzoisothiazolin-3-one (BIT) derivatives was prepared and the anti-bacterial activity of 18 compounds was evaluated. Four sites were targeted on the BIT molecule: the nitrogen and the oxygen atoms on the heterocyclic ring, the C5 and the C6 positions on the aromatic ring. A correlation is suggested between lipophilicity, polarity and antimicrobial activity of the most promising BIT derivatives. Our aim was to establish if by covalently linking a biocide to galactomannans (GM), their "biostability" can be improved and free biocides be decreased or eliminated. Galactomannans (GM) are polysaccharides quite susceptible to microbial contaminations and degradation, have a limited "biostability", thus are supplemented with biocides.